Perbandingan Laju Pertumbuhan Pajak Daerah Sebelum dan Setelah Pandemi Covid-19 di Seluruh Kabupaten/Kota Provinsi NTB - Mantika, Nasywa Ana; Wahyunadi, Wahyunadi (Jurnal Ilmiah Global Education, 2024)
Regional taxes are the largest source of Regional Original Income (PAD). When the Covid-19 pandemic entered Indonesia, regional taxes experienced a very rapid decline. This research aims to determine the comparison before and after the Covid-19 pandemic in West Nusa Tenggara province. The type of research used is descriptive quantitative and this research uses secondary data in the form of Regional Tax Realization Reports for 2017-2022, which were obtained from the official website kemenkeu.go.id and the Central Statistics Agency (BPS). The data will be analyzed using the growth rate contribution analysis formula and will be tested using the paired T-test where this t test is used to compare regional tax growth before and after Covid-19. The results of this research show that there is no difference in regional tax growth between regional tax revenue before and regional tax revenue after the Covid-19 pandemic. This is due to several factors such as the disaster in 2018, namely the earthquake on Lombok Island, and in 2020 the Covid-19 pandemic occurred. So that in testing there was no difference between before and after the pandemic.